Desenvolvimento de biossensor eletroquímico funcionalizado com rodamina 6G para detecção de micobactérias - Riello, Fabiane Nunes (2019)
Methods involving electrochemical detection have shown new possibilities for the diagnosis of various diseases. But they have some limitations. In order to find new ways of modifying the surface of disposable commercial electrodes for adhesion and recognition of biomolecules efficiently and at a lower cost, rhodamine 6G was used for the functionalization of screen-printed graphite electrodes. Mycobacterial samples were used as an experimental model due to the search for new diagnostic techniques more sensitive to infectious diseases. The specific antibody for each mycobacteria was immobilized on the surface of the modified electrodes and samples of tuberculosis culture and Slit-skin smear of contacts and leprosy patients were detected by readings in cyclic voltammetry and voltammetry differential pulse in portable potentiostat. Electrodes modified with rhodamine 6G stabilized the work area of the electrodes and functionalized them for greater adherence of biomolecules. All tuberculosis culture samples were detected and differentiated from other mycobacterial species (except M. avium). The electrochemical biosensor test for M. leprae was shown to be more sensitive with 88,4% sensitivity for the tested Slit-skin smear samples than ELISA (74.4%) and PCR real time (qPCR) (72.1%), laboratory techniques currently used to assist in the diagnosis of Leprosy. The developed biosensor has advantages such as low cost, simplicity in preparation and immobilization, portability, specificity, sensitivity, reproducibility, stability, rapid response and has great potential to be used in the detection, recognition and diagnosis of biomolecules that have carbohydrates in their structure. It is important to emphasize that the developed platform was innovative and pioneer for the detection of M. leprae bacilli and could be incorporated with other diagnostic techniques to identify asymptomatic contacts assisting in the detection and early treatment of leprosy.